Optimization Of Pre-Treatment Conditions Of Acid Blanching And Pectinase In Production Of Papaya Juice - Ariffin, Nurul Anis Jasmin (Pusat Pengajian Teknologi Industri, 2021)
Malaysia is the one of top global producer of papaya fruit. Due to early maturation, high production and high nutritional contents cause the papaya tree widely planted in Malaysia. Carica papaya is a climacteric fruit that will continue to ripen once being plucked from the tree. However, papaya is highly perishable lead to the post-harvest losses. Therefore, ripe papaya can process into papaya juice to improve the shelf life. However, it is difficult to extract the papaya juice due to its high pectin content. The objectives of this study are to produce papaya juice with desired sensory characteristics and consumer acceptance.